MARKETING POLICY AND IT’S IMPACT ON THE CLUB’S BURNING OF ALGERIAN FOOTBALL - BOURAGBA, KOUIDER; RAACH, KAMEL; HAOUDACHI, HARZALLAH (sports creativity, 2025)
International football has known an amazing development in recent years in its access to the word of professional sports , which depends on the economic side in a basic component and a requirement of its most imoprtant requirements, perhaps Algeria has sought to cope with this development , however the economic position of the clubs is not commensurate with the indicators of commensurate with professional indicators ,that is why we deliberately discussed this tagged « Marketing policy and it’s impact on the club’s burning of Algerian football » .Our study aims to know the obstacles of sports marketing for Algerian football clubs , and how imoptant it is to improve the financial aspect and how much to develop sports results ,based on the nature of the topic , a descriptive approach was chosen that is appropriate for the research , a random sample was chosen from the community of players ,coaches and managers in the first professionl Algerian football clubs ,and based on the research hypothesis we relied on the questionnaire as a tool to collect data ,we reached in this research except that the marketing policy in Algerian football clubs is not successful due to the limited understanding and understanding of its importance and the lack of qualified and specialized expertise ,in addition to the financial obstacles that prevented sports marketing support ,whitch reflected negatively on the sports results for Algerian soccer clubs .